Enfermería: beatitud, autonomía y responsabilidad (Salud, Arte y Cuidado, 2019)
The present literature review seeks to answer the following question: Is the nursing staff able to perform actions without relying on medical orders? Based on the history of the formation of the career, in its curriculum of study and currently in the different specializations that exist for the development of this profession we can realize that the nurses perform unique, independent and specific tasks protected by legal bases and applying the scientific method is reached the conclusion of the irrefutable autonomy that this staff presents in the development of their work.
Keywords: Nursing; Autonomy; Medical Orders